2019
DOI: 10.1155/2019/6372503
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of Solar Carport Canopies for Maximum Power Generation and Efficiency at Bahawalpur

Abstract: In recent years, the upturn demand of electricity and the generation of electrical power demand from fossil fuels are increasing day by day which results in environmental impacts on the atmosphere by greenhouse gases, and a high cost of electric power from these sources makes it unaffordable. The use of renewable energy sources can overcome this problem. Therefore, in this work, we present a solution by implementing the solar car parking lots. A detailed work has been done for solar car parking site selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In [5] 923 effectiveness if they are implemented together. In [6] A detailed work has been done for solar car parking site selection and maximum solar electric power generation and its capacity effects with the shading of nearby trees and buildings by using the HelioScope online software developed by Folsom Labs, it is found that the monopitch canopy is the best to mount at solar car parking lots. Other related works could be found in [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In [5] 923 effectiveness if they are implemented together. In [6] A detailed work has been done for solar car parking site selection and maximum solar electric power generation and its capacity effects with the shading of nearby trees and buildings by using the HelioScope online software developed by Folsom Labs, it is found that the monopitch canopy is the best to mount at solar car parking lots. Other related works could be found in [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Umer et al in the paper [21] designed and optimized Solar Carport Canopies for maximum power generation and efficiency at Bahawalpur. In this project, solar car parking lots were implemented.…”
Section: Use Of Solar Power For Generation Of Electricitymentioning
confidence: 99%
“…There are multiple types of engineered structures for surface parking dependent on solar energy; fig. 5 the most efficient of all is duopitch canopy V-frame double row structure as it has ample space in between the V -shaped structures for charging system equipment to install [4].…”
Section: Vehicle Parking Cum Charging Lotsmentioning
confidence: 99%